2000
DOI: 10.1016/s0022-5347(05)67145-5
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Dna Sequences in Prostate Tissue From Patients With Prostate Cancer and Chronic Prostatitis

Abstract: Bacterial DNA sequences may be identified in prostate tissue from many patients. Bacterial detection rates in prostate tissue appear to differ among populations, with higher rates among patients with the chronic prostatitis/pelvic pain syndrome than among those with prostate cancer. Future studies of the role of various bacteria in the prostate may provide insight into the pathophysiology of prostate disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Prostate tissue secretes immunosuppressive proteosomes (44) and seminal fluid contains high levels of immunosuppressive prostaglandins (45), which may hamper the development of humoral antibody response even in cases in which C. trachomatis is present in the tissue. This could be studied by direct demonstration of the agent in prostatic tissue (46,47) which was not available in the present study. Immunologic mechanisms might explain the lack of positive association but are not credible explanations of the inverse relationship observed.…”
Section: Discussionmentioning
confidence: 96%
“…Prostate tissue secretes immunosuppressive proteosomes (44) and seminal fluid contains high levels of immunosuppressive prostaglandins (45), which may hamper the development of humoral antibody response even in cases in which C. trachomatis is present in the tissue. This could be studied by direct demonstration of the agent in prostatic tissue (46,47) which was not available in the present study. Immunologic mechanisms might explain the lack of positive association but are not credible explanations of the inverse relationship observed.…”
Section: Discussionmentioning
confidence: 96%
“…Many previous studies have attempted to evaluate the bacterial flora present within the prostate using prostate tissue either from biopsies or whole-gland sections (80). However, there also has been variability in how patients were categorized as having CP/CPPS (81). In one study of men with CP/CPPS, it was hypothesized that the local microbiota of the prostate in CP/CPPS patients would be different than that of controls, either due to or being the cause of an inflammatory process within the tissue.…”
Section: The Microbiome In Urologic Chronic Pain Syndromesmentioning
confidence: 99%
“…In a subsequent study Kreiger found the 16S rRNA gene product in 20% of 107 patients with prostate cancer as compared to 46% of 170 men with chronic prostatitis. The median age of the men with prostate cancer was 64 and the median age of the men with prostatitis was 38 [8]. Essentially it is difficult to obtain aged matched controls to undergo a prostatic biopsy.…”
Section: Introductionmentioning
confidence: 99%